Defects with deep donor and acceptor levels in nanocrystals of CdTe and CdSe - Babentsov, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
The defects in CdTe and CdSe nanocrystals were studied by comparing the photoluminescence spectra and cyclic voltammetry dependences, which enabled us to identify two main electron levels in CdTe and four in CdSe NCs. In CdTe nanocrystals these levels are: a hole trap at the energy EV + 0.5 eV and an electron trap at Ec – 0.5 eV. In CdSe nanocrystals, detected were two hole traps at Ev + 0.52 eV and Ev + 0.8 eV, and two electron traps at Ec – 0.25 eV and Ec – 0.65 eV. The 2+/1+ level of VCd or Tei is suggested to be an acceptor, and the 2–/1– level of an antisite defect is suggested to be a donor level.